Hubungan Standar Pelayanan Minimal Gizi dengan Tingkat Kepuasan Pasien Rawat Inap di Rumah Sakit Islam Muhammadiyah Sumberrejo Kabupaten Bojonegoro - Alya Afirsta Rahmadani; Rita Ismawati (Jurnal Ilmu Kesehatan dan Gizi, 2025)
Patient satisfaction is one of the benchmarks for assessing a hospital's success in providing services. Quality targets in nutrition services based on hospital Minimum Service Standards include three indicators, namely timeliness of food distribution, food waste and the absence of errors in diet administration. The aim of this research is to determine the relationship between minimum nutritional service standards and the level of satisfaction of inpatients at the Muhammadiyah Islamic Hospital Sumberrejo, Bojonegoro Regency. This type of research is cross-sectional. The sample in this study was patients in classes 2 and 3 of the Shafa and Marwah inpatient rooms, totaling 135 patients. The data measured are the level of patient satisfaction, timeliness of food distribution, accuracy of diet and food waste. Bivariate analysis used the Spearman's Rank test. The results of data analysis showed that food distribution timeliness was 92.5%, diet accuracy was 98%, food waste was 15.1%, while patient satisfaction levels were very satisfied (52%), satisfied (44%), dissatisfied (2%) and very dissatisfied (1%). The results of the study showed that the timeliness of distribution of breakfast (p=0.864>0.05), afternoon (p=0.853>0.05), evening (p=0.864>0.05) and the level of satisfaction, while the accuracy of the diet and the level of satisfaction patients (p=0.112>0.05), for food waste and level of patient satisfaction (p=0.311>0.05). From this research it can be concluded that statistically there is no significant relationship between minimum service standards (timeliness of food distribution, accuracy of diet and food waste) and the level of patient satisfaction. Suggestions that can be given in this research are that hospital efforts are needed to maintain the quality of food services by paying more attention to the accuracy of diet for patients.